Mahakam Ulu Regency and The Muslim Minority: Strategies for Sustaining Islamic Communities in Religious Life - Akbar, Paisal; Qodir, Zuly; Jubba, Hasse; Nurmandi, Achmad; Mutiarin, Dyah; Usman, Sunyoto (Millati: Journal of Islamic Studies and Humanities, 2025)
Minority religious communities often face significant challenges and social friction in various aspects of life. In Indonesia, several regions have a minority Muslim population; Mahakam Ulu Regency is one of them. This study aims to understand how the Islamic community in Mahakam Ulu Regency is undergoing religious rituals and living a life of religious tolerance. The research data consisted of primary and secondary data, with the primary data being semi-structured interviews conducted with several informants of Islamic religious leaders in Mahakam Ulu Regency. Meanwhile, secondary data is produced from reports of government agencies to meet the data needs of this study. The interview data were then processed using NVivo 12 Plus. The results of the study are divided into two sub-parts. In the first part, we map the secondary data obtained by identifying pockets of the Islamic population in each area of Mahakam Ulu Regency and then focusing on them. In the second part, we analyzed the strategies carried out by the Islamic community of Mahakam Ulu Regency so that they can continue to carry out religious rituals and can exist in a living social and economic life in Mahakam Ulu Regency. Some of the strategies carried out are by limiting the culture of worship by restricting loudspeakers used in mosques in Mahakam Ulu Regency, so that when the azan resounds, prayers are carried out without using a high volume of sound. Besides that, another strategy is to increase tolerance and concern for all elements of society, regardless of their religious background.